Management of acute ischemic stroke in patients with COVID-19 infection: Report of an international panel - Qureshi, Adnan, I; Abd-Allah, Foad; Alsenani, Fahmi; Aytac, Emrah; Borhani-Haghighi, Afshin; Ciccone, Alfonso; Wang, Yongjun (Sage Publications Ltd, 2020)
Background and purpose On 11 March 2020, World Health Organization (WHO) declared the COVID-19 infection a pandemic. The risk of ischemic stroke may be higher in patients with COVID-19 infection similar to those with other respiratory tract infections. We present a comprehensive set of practice implications in a single document for clinicians caring for adult patients with acute ischemic stroke with confirmed or suspected COVID-19 infection. Methods The practice implications were prepared after review of data to reach the consensus among stroke experts from 18 countries. The writers used systematic literature reviews, reference to previously published stroke guidelines, personal files, and expert opinion to summarize existing evidence, indicate gaps in current knowledge, and when appropriate, formulate practice implications. All members of the writing group had opportunities to comment in writing on the practice implications and approved the final version of this document. Results This document with consensus is divided into 18 sections. A total of 41 conclusions and practice implications have been developed. The document includes practice implications for evaluation of stroke patients with caution for stroke team members to avoid COVID-19 exposure, during clinical evaluation and performance of imaging and laboratory procedures with special considerations of intravenous thrombolysis and mechanical thrombectomy in stroke patients with suspected or confirmed COVID-19 infection. Conclusions These practice implications with consensus based on the currently available evidence aim to guide clinicians caring for adult patients with acute ischemic stroke who are suspected of, or confirmed, with COVID-19 infection. Under certain circumstances, however, only limited evidence is available to support these practice implications, suggesting an urgent need for establishing procedures for the management of stroke patients with suspected or confirmed COVID-19 infection.
Keywords: Coronavirus; COVID-19; acute stroke; mechanical thrombectomy; thrombolysis; ischemic stroke